THE CHARACTER OF ʿALĪ IN THE POEMS OF NĀSIR-I KHUSRAW AND SANĀ'Ī GHAZNAVĪ - Aygün Alizade (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2023)
Ali ibn Abi Talib was a person with so great magnificence that almost all poets, especially those who wrote gnostic works, always tried to show peculiarities of his personality. Among these poets Nasir Khusrow and Sanai Ghaznavi should be mentioned specially. A comprehensive study of the character of Ali in works of Nasir Khusrow and Sanai Ghaznavi is subject to a voluminous research work. Main purpose of the article is particular research of every couplet devoted to Ali by Nasir Khusrow and Sanai Ghaznavi and detection of their sympathy for Ali. One of the poems written by Sanai Ghaznavi and praising Ali is “Adoration for Ali ibn Abi Talib” in the 24th Part of the 3rd Section of “Hadigat al-Haqiqa va Shariat al-Tariqah” (The Garden of Truth and the Path to Trek). The research work includes study of Nasir Khusrow’s couplets in his “Diwan” with similar meaning, while Sanai’s abovementioned poem has been chosen as a basis for comparison. Personality of Ali is visualized while reading Sanai’s poem consisting of 187 couplets. After a brief research on life and works of the Ismaili poet Nasir Khusrow and the gnostic poet Sanai Ghaznavi, historical personalty and moral features of Ali has been subject to research in the article. Ali’s mutual relation with the Prophet, conquest of Khaybar, his valor in the battles of Jamal and Siffin and his Zulfiqar has been subject presented as his historical personality, while his wisdom, watchfulness, piety and generosity has been included in his moral features. Couplets of the poem have been organized systematically and in accordance with the topics. At the same time, the Nasir Khusrow’s relevant couplets also have been presented in this regard. Furthermore, the two poets’ couplets introducing and praising Ali ibn Abi Talib on the basis of Koranic verses and sayings of the Prophet have been subject to the study additionally. As a result of our studies, we can conclude that both Nasir Khusrow and Sanai Ghaznavi not only showed people Ali’s virtues and magnificence in every sphere, but also tried to assume that a close approach to Ali was necessary in order to learn and know Islamic rules, religious law and interpretation of Koran, as columns of the religion after the Prophet’s passing were the Book and his family. Sayings cited from the Prophet, Koranic verses and Nahj al-Balagha can show us that Ali was a person with high virtues. Devoting poems to Ali, Nasir Khusrow and Sanai Ghaznavi actually desired that all people take this perfect person an example for themselves. Only love to a God chosen prophet can pave the way for formation of a personality like Ali – an opinion that can be traced in the poems. As shown in the poems, Ali accumulated so many virtues in himself that the world became smaller and fitted tight for him. Sanai writes that Ali did not tie himself to the world with strong ties and so he was really free and such a free spirit bestowed him the mentioned virtues. Nasir Khusrow, in his turn, goes further, naming Ali “the rope of God” and calling readers to drop the rope of the world and to catch Ali’s rope.